Wolves choose ambushing locations to counter and capitalize on the sensory abilities of their prey. (9th February 2021) - Gable, Thomas D; Homkes, Austin T; Johnson-Bice, Sean M; Windels, Steve K; Bump, Joseph K
Abstract: Comprehensive knowledge of ambush behavior requires an understanding of where a predator expects prey to be, which is generally unknowable because ambush predators often hunt mobile prey that exhibit complex, irregular, or inconspicuous movements. Wolves ( Canis lupus ) are primarily cursorial predators, but they use ambush strategies to hunt beavers ( Castor canadensis ). Terrestrial beaver activity is predictable because beavers use well-defined, conspicuous habitat features repeatedly. Thus, studying where wolves wait-in-ambush for beavers provides a unique opportunity to understand how predators choose ambush locations in relation to prey activity. We searched 11 817 clusters of GPS locations from wolves in the Greater Voyageurs Ecosystem, International Falls, MN, and documented 748 ambushing sites and 214 instances where wolves killed beavers. Wolves chose ambush locations: 1) with olfactory concealment to avoid detection from the highly developed olfactory senses of beavers and 2) close (generally <5 m) to beaver habitat features to take advantage of beavers' inability to visually detect motionless predators. Our work describes in detail the ambush strategies wolves use to hunt beavers and continues to overturn the traditional notion that wolves rely solely on cursorial hunting strategies. We also demonstrate that ambush predators can anticipate the movements and behavior of their prey due to a fundamental understanding of their prey's sensory abilities. Wolves, therefore, and likely ambush predators in general, appear capable of simultaneously accounting for abiotic and biotic factors when choosing ambush locations, ultimately allowing them to counter and capitalize on the sensory abilities of their prey. Abstract : Understanding where and how ambush predators choose ambushing locations is difficult because it requires understanding where ambush predators expect prey to be, which is often unknowable. By studying where wolves waited-in-ambush for beavers, we show ambush predators can: 1) anticipate the movements and behavior of their prey due to a fundamental understanding of their prey's sensory abilities and 2) counter and capitalize on their prey's sensory abilities by choosing ambushing locations that simultaneously account for environmental and biological factors.